IMPLEMENTASI PENDEKATAN PEMBELAJARAN YANG BERBASIS PENGALAMAN LOKAL (LOCAL WISDOM) DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS - Isnaini Ulfa Intan ‘Arifani; Meisya Nurkhalifa; Muhammad hafiz; Reyhan Prayuga; Mukhtar Latif (STKIP Subang, 2026)
The implementation of a learning approach based on local wisdom in Islamic Religious Education is one strategy for enhancing the relevance of learning to students’ lives. Learning that integrates local cultural values not only strengthens students’ understanding of the subject matter but also contributes to character development, religious attitudes, and a love for local culture. This study aims to describe the implementation of a local wisdom-based learning approach in Islamic Religious Education courses at high schools and to identify its benefits for the learning process. The study employs a qualitative method, specifically a literature review. Data were obtained through a review of various scholarly sources, including books, national and international journal articles, conference proceedings, and documents relevant to the concepts of local wisdom and Islamic Religious Education. Data analysis was conducted through the stages of data collection, reduction, presentation, and drawing conclusions from the literature review. The results of the study indicate that the application of a local experience-based learning approach is capable of connecting Islamic Religious Education material to the real-life context of students through the utilization of cultural values, traditions, and local wisdom that have developed within the community. This approach enhances student engagement, strengthens understanding of religious concepts, and fosters religious character, tolerance, responsibility, and a commitment to preserving local culture. Thus, the local-experience-based learning approach can serve as an effective contextual learning alternative for improving the quality of Islamic Religious Education in high schools